Characterisation of germplasm accessions of Napier grass (Pennisetum purpureum and P. purpureum x P. glaucum hybrids) and comparison with farm clones using RAPD - Lowe, A.J.; Thorpe, W.R.; Teale, A.J.; Hanson, Jean (2003)
Fifty six germplasm accessions of the important East African fodder crop Napier grass, Pennisetum purpureum, and its hybrids with P. glaucum, were characterised using 67 random amplified polymorphic DNA (RAPD) fragments. No or very low intra-accession variation was found for 49 of the accessions examined, confirming field observations that this species is predominantly clonally propagated. Comparison of intra and inter-accession variation identified several groups of identical/similar accessions that could be targeted if the collection is to be rationalised, and also highlighted two misplantings of germplasm material during transfer to a field trial site. A neighbour joining dendrogram of Jaccard's similarity estimates, clearly separated 50 accessions of P . purpureum from three P . glaucum individuals, and placed six hybrid accessions in an intermediate position. These groupings were well supported by a nested AMOVA (P <0.001; 29.5% of total variance due to taxonomic delineation). The main group of P. purpureum individuals could be further differentiated into five sub-groups (designated East Africa, Southern Africa, USA1, USA2 and Miscellaneous, to reflect the majority membership of sub-groups) and examination of the within P. purpureum component of the nested AMOVA, found them to be significantly different (P<0.001; 18.8% of variance). Genetic diversity across all accessions was found to be fairly high (Shannon's diversity index 0.306) and thus the collection probably represents a wide genetic base for this species. In addition to germplasm accessions, 25 Kenyan farm clones were also analysed. A principal coordinate analysis found that all but one of the clones clustered with the main P. purpureum group of accessions, indicating that the majority are probably not interspecific hybrids. The origin and pedigree of clones is discussed based on genetic similarity amongst clones and to germplasm accessions.